ANALISIS TINGKAT PENGETAHUAN DAN RELIGIUSITAS MAHASISWA AKUNTANSI TERHADAP RIBA - Bagus Ainuddin Jarkesi; Afifudin Afifudin; Hariri Hariri (Universitas Islam Malang, 2021)
The purpose of this study was to determine the effect of the level of knowledge and religiosity on Riba. The dependent variable in this study is Riba. The independent variables in this study are the level of knowledge and religiosity. This research is a quantitative research. The data used in this study are primary data obtained from distributing questionnaires to accounting students at the Faculty of Economics and Business, Islamic University of Malang. The data analysis technique used in this study was multiple linear regression analysis. The results of the analysis show that partially the knowledge variable and the religiosity variable have a positive effect on the usury variable.Keywords: Knowledge, religiosity, Riba